PENINGKATAN KONTROL DIRI SISWA DALAM BERMEDIA SOSIAL MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SELF MANAGEMENT - Ilham Sholikul Hadi; Sucipto Sucipto; Edris Zamroni (Universitas Muria Kudus, 2022)
Research purposes: 1. Explaining the implementation of self-management technique group guidance can improve self-control in social media in class XI students of SMK Negeri 1 Kudus in the academic year 2022/2023. 2. To find out the increase in self-control in social media through group guidance on self-management techniques in class XI students of SMK Negeri 1 Kudus in the 2022/2023 academic year. Using the type of guidance and counseling action research (PTBK). The subjects of this study were 8 students of class XI with low self-control in social media. Methods of data collection by observation, interviews and documentation. Using qualitative descriptive analysis. The results of the study were the implementation of group guidance for two cycles with 6 meetings, applying self-management techniques with the stages of self-monitoring, self-evaluation, and giving reinforcement, elimination or punishment. There was a significant increase in student self-control in social media after being provided with services.